Stress and Coping Mechanism Among Nursing Students of a Selected Tertiary Care Centre of West Bengal - Sarkar, Manisha; Mahapatra, Subarna Sinha; Sarkar, Aditya Prasad; Biswas, Atanu (National Journal of Community Medicine, 2023)
Background: The health of nursing students are affected by different stressors. The perception of and the ability to handle the stress depends on their coping styles. Objectives: To find the prevalence of stress and factors associated with stress and coping mechanisms among B.Sc. nursing students of Nursing College, at Bankura, West Bengal. Methodology: A cross-sectional observational study was conducted among 201 B.Sc. nursing students of a tertiary care centre at Bankura using self-administered questionnaire, PSS-10 and Brief-COPE inventory. Association between categorical data were analysed using chi square test. Correlation between two quantitative variables was tested using Spearman’s rank correlation, while Mann Whitney U test was performed to compare the differences between two groups. Results: Proportion of participants with low, moderate and high perceived stress were 18.9%, 67.2% and 13.9% respectively. Higher academic year, opting career by compulsion, history of long-term illness and receiving no support from family were associated with high stress. There was significant positive correlation between age, problem focused coping, avoidant coping, adaptive coping and maladaptive coping scores with PSS-10. Conclusions: Complete stress-free nursing career might be a stretch, but it is imperative to identify the stressors to alleviate the level of perceived stress among the nursing students.